INNOVATIVE MODELS OF TRAINING FUTURE TEACHERS OF FINE ARTS BASED ON AN INDIVIDUAL APPROACH (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article analyzes innovative models of an individual approach, in particular the role of STEAM and cluster technologies in the process of training future teachers of fine arts. The experience of involving students in research and creative activities is illustrated by the example of the “Teaching and Learning” project, the mentor-student system, and creative centers such as “Art Studio” implemented at the Department of “Fine Arts and Design” of Chirchik State Pedagogical University.